(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
The Quadrilha de Piaba troupe, a group composed of students and a professor from the Investigation of Epic Scene Project course in the Theater Licentiate program at Unespar, shares its poetic investigations on class struggle within the context of the relentless precarization of labor through the play "Give It All!" (Entrega Tudo!). The work draws from Brecht’s studies on epic theater and his play The Exception and the Rule (A exceção e a regra). The aim of this text is to share and reflect on the experience of creating this production, which encompasses the development of a collective artistic and pedagogical process, in dialogue with the works of Abreu (2000), Carleto (2024), and Mate (2021).